Analysis of Peer Friendship, Learning Interests, and Biology Learning Results of Class X Students at Plus Bustanul Ulum Puger Jember Senior High School - Sholihah, Luluk Rodiatus; Nasution, Nanda Eska Anugrah; Rizka, Chairany (META: Journal of Science and Technological Education, 2024)
The aim of this study is to provide a comprehensive analysis of the characteristics of peer friendships, the level of interest in learning, and the academic results in biology of class X students enrolled at SMA Plus Bustanul Ulum Puger Jember during the academic year 2022/2023. The research methodology employed in this study is quantitative and descriptive, utilizing survey techniques. The subjects of this study consisted of students in the tenth grade at SMA Plus Bustanul Ulum. The research employed a non-probability sampling technique known as total sampling, which involved selecting all 86 class X pupils as the sample. The research employed interviews, questionnaires, and documentation as data gathering methods. The questionnaire employed a Likert scale. All instruments employed were verified to be both valid and reliable. The study revealed that the mean student peer friendship score was 74% in the high range, the mean student's interest in learning score was 69% in the high range, and the mean student learning result score was 75% in the high range. Peer friendships, interest in learning, and biology learning results for grade X students at SMA Plus Bustanul Ulum Puger Jember are significantly high throughout the 2022/2023 academic year. Researchers propose conducting additional investigation to ascertain the correlation among the three variables. The researchers recommend further investigation to determine the correlation among the three variables.